The ideology of consumerism in the works of Andy Warhol / Идеология консюмеризма в творчестве Энди Уорхола - Elena Iakovleva / Елена Людвиговна Яковлева (Индустрии впечатлений: Технологии социокультурных исследований)
The object of the study was the works of Andy Warhol, viewed through the prism of the ideology of consumerism. Biographical and analytical methods were chosen as research methods. Andy Warhol, having combinined the ideology of consumerism, advertising and art in his work, presented his own vision of things / faces of modernity, becoming a successful commercial artist. Warhol's canvases, which have a serial character thanks to the silkscreen technique, advertised the immediate beauty of things /faces, were put into circulation and introduced people as potential consumers to current trends. Stamping many copies of the same image made the artist quite rich and famous, and Warhol's numerous provocative acts turned him into a popular media face who profited from literally everything. Behind the apparent banality of the artist's works are hidden the ideas of the frailty of life and the momentary nature of current trends. But Andy veils them through irony, a positive attitude to everything and provocative behavior. All of the above testifies to the crisis of the being an artist who carefully follows the ideology of consumerism and at the same time rebels against it. Объектом исследования стало творчество Энди Уорхола, рассматриваемое через призму идеологии консюмеризма. Методами исследования избраны биографический и аналитический. Энди Уорхол, соединив в своем творчестве идеологию консюмеризма, рекламу и искусство, представил собственное видение вещей/лиц современности, став успешным коммерческим художником. Уорхоловские полотна, обладающие серийным характером благодаря технике шелкографии, рекламировали непосредственную красоту вещей/лиц, запускались в тираж и приобщали людей как потенциальных потребителей к актуальным тенденциям. Штамповка множества экземпляров одного и того же изображения сделала художника довольно богатым и знаменитым человеком, а многочисленные провокационные поступки превратили Уорхола в популярное медийное лицо, которое извлекало выгоду буквально из всего. За видимой банальностью работ художника скрываются идеи бренности жизни и сиюминутности актуальных тенденций. Но Уорхол вуалирует их посредством провокационного поведения, использования иронии, положительного отношения ко всему. Перечисленное свидетельствует о кризисе бытия художника, тщательно следующего идеологии консюмеризма и одновременно бунтующего против нее.